Solutions For Community-Based Tourism Development In The Mekong Delta Region - Le Thi Ngoc Van; Quoc Nghi Nguyen; Le Thi Khanh Duy (Cita konsultindo, 2026)
This study was conducted to propose solutions for community-based tourism development in the Mekong Delta region (MDR). Qualitative research methods (expert consultation and SWOT matrix analysis) were used to address the research objectives. Research results show that community-based tourism in the MDR has achieved many positive accomplishments in recent decades, with numerous community tourism spots establishing attractive brands in the minds of both domestic and international tourists. However, limitations in human resource capacity, regional connectivity, product diversity, and the impact of climate change have hindered the development of this tourism type. Consequently, the study proposes several solutions for community-based tourism development in the MDR, including (i) Developing distinctive community-based tourism products associated with the riverine and orchard culture, (ii) Enhancing human resource training and management capacity for community-based tourism, (iii) Investing in infrastructure development and digital transformation in destination management, and (iv) Strengthening public-private linkages and international cooperation for sustainable community-based tourism development